Inventory of Spice Plants Based on Vegetative Organs in the Lower Siantan Region - Aldiansyah, Rifki; Kumalasari, Muthia; Rianita, Desi; Rusdeviani, Rusdeviani (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The background to this research is that the knowledge of the people in Siantan Hilir is still quite limited in identifying spices, so that information from one community to another in one area can be different. The research aims to provide knowledge to the public regarding plant descriptions including: local names, scientific names of plants, and plant vegetative organs. The research was carried out in Siantan Hilir Village, using observation methods, sampling and field data recording. The research results showed that the plants found were quite diverse and most were from the Zingiberaceae family. Existing information can be used as learning material and reference for determining a spice plant species based on the characteristics and morphology described in the article.